2022
DOI: 10.3390/cancers14112572
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem-Cell Transplantation for High-Risk Neuroblastoma: Historical and Critical Review

Abstract: Curing high-risk neuroblastoma (HR-NB) is a challenging endeavor, which involves the optimal application of several therapeutic modalities. Treatment intensity for cancer became highly appealing in the 1990s. Investigative trials assumed that tumor response correlated with the dosage or intensity of drug(s) administered, and that this response would translate into improved survival. It was postulated that, if myelotoxicity could be reversed by stem-cell rescue, cure might be possible by increasing the dose int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Unfortunately, chemotherapy has many side effects and, particularly, myelotoxicity has been evaluated as the most dose-limiting toxicity for chemotherapeutic agents [ 88 ]. For this reason, the possibility of rescuing the stem cells from the patient and performing autologous stem cell transplantation (ASCT) after high-dose treatment could highly impact therapy outcome [ 89 , 90 ]. Many studies demonstrated how single [ 56 , 91 ] or more recent tandem transplantation [ 92 ] post-chemotherapy can increase event-free survival compared to chemotherapy alone, having a particular impact on HR-NB patients’ outcome.…”
Section: Current Therapies Of High-risk Neuroblastomamentioning
confidence: 99%
“…Unfortunately, chemotherapy has many side effects and, particularly, myelotoxicity has been evaluated as the most dose-limiting toxicity for chemotherapeutic agents [ 88 ]. For this reason, the possibility of rescuing the stem cells from the patient and performing autologous stem cell transplantation (ASCT) after high-dose treatment could highly impact therapy outcome [ 89 , 90 ]. Many studies demonstrated how single [ 56 , 91 ] or more recent tandem transplantation [ 92 ] post-chemotherapy can increase event-free survival compared to chemotherapy alone, having a particular impact on HR-NB patients’ outcome.…”
Section: Current Therapies Of High-risk Neuroblastomamentioning
confidence: 99%
“…HSC therapy for different diseases ( Hifumi et al, 2017 ; Morgan et al, 2017 ; Giannaccare et al, 2020 ; Wu et al, 2020 ) including cancer has been intensively explored and practiced such as leukemia and neuroblastoma ( Daver et al, 2020 ; Mora, 2022 ). Also, certain characteristics of the young mice could be transferred to old mice via heterochronic parabiosis or heterochronic transplantation ( Conboy et al, 2005 ; Das et al, 2019 ; Goodell and Rando, 2015 ; Kang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell therapy for different diseases [47][48][49][50] including cancer has been intensively explored and practiced such as leukemia, and neuroblastoma, etc 51,52 . Also, certain characteristics of the young mice could be transferred to old mice via heterochronic parabiosis or heterochronic transplantation [53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%